Design and Implementation of a Microcontroller Based DC/AC Inverter (مجلة المنصور, 2022)
In this paper, a method is proposed to improve the frequency stability and accuracy of the generated wave in DC/AC square wave inverters using a microcontroller-based stabilized oscillator circuit. The proposed technique relies on using the 8051 microcontroller as a stable oscillator to generate two anti-phase 50 Hz square waves for the driving power stage of the inverter based on a program stored in its internal ROM. These signals are then boosted to increase their voltage and current levels using BJT switching mode power transistors operating in the push/pull mode. The resulting signal is then raised into the required voltage level with the aid of a step-up transformer. A practical inverter circuit has been designed and constructed to convert a 12 V battery DC input into 220 V AC output based on the 8051 microcontroller. This circuit consists of an 8051 microcontroller, buffer, driver power transistor stage, final power transistor stage, and a step-up transformer. The inverter circuit has been simulated, implemented, and tested practically. The test measurements have indicated that the circuit gives a full load power of 10 W with full-load voltage regulation of 8%, and a maximum conversion efficiency of 70%.